What role should randomized control trials play in providing the evidence base for conservation?. Issue 2 (24th March 2021) - Pynegar, Edwin L.; Gibbons, James M.; Asquith, Nigel M.; Jones, Julia P. G.
Abstract: The effectiveness of many widely used conservation interventions is poorly understood because of a lack of high-quality impact evaluations. Randomized control trials (RCTs), in which experimental units are randomly allocated to treatment or control groups, offer an intuitive way to calculate the impact of an intervention by establishing a reliable counterfactual scenario. As many conservation interventions depend on changing people's behaviour, conservation impact evaluation can learn a great deal from RCTs in fields such as development economics, where RCTs have become widely used but are controversial. We build on relevant literature from other fields to discuss how RCTs, despite their potential, are just one of a number of ways to evaluate impact, are not feasible in all circumstances, and how factors such as spillover between units and behavioural effects must be considered in their design. We offer guidance and a set of criteria for deciding when RCTs may be an appropriate approach for evaluating conservation interventions, and factors to consider to ensure an RCT is of high quality. We illustrate this with examples from one of the few concluded RCTs of a large-scale conservation intervention: an incentive-based conservation programme in the Bolivian Andes. We argue that conservation should aim to avoid a rerun of the polarized debate surrounding the use of RCTs in other fields. Randomized control trials will not be feasible or appropriate in many circumstances, but if used carefully they can be useful and could become a more widely used tool for the evaluation of conservation impact.